Clinical outcomes with a low add multifocal and an extended depth of focus intraocular lenses both implanted with mini-monovision - TOKER, AYŞE EBRU; SEVİK, MEHMET ORKUN (SPRINGERNATURE, 2022)
Objectives To compare the visual acuity, contrast sensitivity (CS), spectacle needs, photic phenomena, and quality of life parameters of patients bilaterally implanted with a low add multifocal (MIOL) or an extended depth of focus (EDOF) intraocular lens (IOL), both with intended mini-monovision. Methods In this prospective, randomized, comparative study, patients were randomized to receive either Tecnis +2.75 D (ZKB00) (MIOL Group, n = 15) or Tecnis Symfony (ZXR00) (EDOF Group, n = 14) for bilateral implantation with mini-monovision (-0.50 D). Binocular logMAR uncorrected visual acuities (UVA), monocular defocus curves, CS with CSV 1000-E, and Pelli-Robson Test (PRT), spectacle needs and quality of life parameters with NEI RQL-42 questionnaire were evaluated at postoperative 1, 3, and 6 months. Results Results of MIOL and EDOF Groups at postoperative month 6 are as follows: distance (6 m) UVA -0.03 +/- 0.05 and -0.05 +/- 0.06 (p = 0.938), intermediate (60 cm) UVA, 0.04 +/- 0.08 and -0.03 +/- 0.07 (p = 0.046); near (40 cm) UVA, 0.22 +/- 0.08 and 0.15 +/- 0.07 (p = 0.046); near spectacle needs, 26.7% and 14.3% (p > 0.05), respectively. Better visual acuity was achieved in the EDOF Group between the defocus range of -0.50 and -1.75 D (p < 0.05). No significant difference was found regarding photic phenomena and CS evaluated with CSV 1000-E between the two IOL groups at 6 months after surgery (otherwise there are differences at 1 and 3 months in favor of EDOF). However, EDOF Group performed better in mesopic CS evaluated with PRT (p < 0.05). Conclusions When implanted with mini-monovision better binocular uncorrected visual performance at intermediate and near distances achieved with EDOF than low add MIOL.
Keywords: BILATERAL IMPLANTATION; VISUAL OUTCOMES; CONTRAST SENSITIVITY; NORMAL VALUES; RANGE; VISION; PERFORMANCE; QUALITY; ACUITY